Engagement With a Health Information Technology-Augmented Self-Management Support Program in a Population With Limited English Proficiency: Observational Study - Machen, Leah; Handley, Margaret A; Powe, Neil; Tuot, Delphine (JMIR Publications, 2021)
BackgroundLimited English proficiency (LEP) is an important driver of health disparities. Many successful patient-level interventions to prevent chronic disease progression and complications have used automated telephone self-management support, which relies on patient activation and communication to achieve improved health outcomes. It is not clear whether these interventions are similarly applicable to patients with LEP compared to patients with English proficiency. ObjectiveThe objectives of this study were as follows: (1) To examine the impact of LEP on patient engagement (primary outcome) with a 12-month language-concordant self-management program that included automated telephone self-management support, designed for patients with chronic kidney disease (CKD). (2) To assess the impact of LEP on change in systolic blood pressure (SBP) and albuminuria (secondary outcomes) resulting from the self-management program. MethodsThis was a secondary analysis of the Kidney Awareness Registry and Education (KARE) pilot trial (NCT01530958) which was funded by the National Institutes of Health in August 2011, approved by the University of California Institutional Review Board in October 2011 (No. 11-07399), and executed between 2013 and 2015. Multivariable logistic and linear models were used to examine various facets of patient engagement with the CKD self-management support program by LEP status. Patient engagement was defined by patient's use of educational materials, completion of a health coaching action plan, and degree of participation with automated telephone self-management support. Changes in SBP and albuminuria at 12 months by LEP status were determined using multivariable linear mixed models. ResultsOf 137 study participants, 53 (38.7%) reported LEP, of which 45 (85%) were Spanish speaking and 8 (15%) Cantonese speaking. While patients with LEP and English proficiency similarly used the program's educational materials (85% [17/20] vs 88% [30/34], P=.69) and completed an action plan (81% [22/27] vs 74% [35/47], P=.49), those with LEP engaged more with the automated telephone self-management support component. Average call completion was 66% among patients with LEP compared with 57% among those with English proficiency; patients with LEP requested more health coach telephone calls (P=.08) and had a significantly longer average automated call duration (3.3 [SD 1.4] min vs 2.2 [1.1 min], P<.001), indicating higher patient engagement. Patients with LEP randomized to self-management support had a larger, though nonstatistically significant (P=.74), change in SBP (-4.5 mmHg; 95% CI -9.4 to 0.3) and albuminuria (-72.4 mg/dL; 95% CI -208.9 to 64.1) compared with patients with English proficiency randomized to self-management support (-2.1 mmHg; 95% CI -8.6 to 4.3 and -11.1 mg/dL; 95% CI -166.9 to 144.7). ConclusionsPatients with LEP with CKD were equally or more engaged with a language-concordant, culturally appropriate telehealth intervention compared with their English-speaking counterparts. Augmented telehealth may be useful in mitigating communication barriers among patients with LEP. Trial RegistrationClinicalTrials.gov NCT01530958; https://clinicaltrials.gov/ct2/show/NCT01530958